Optimal microgrid’s protection coordination considering N-1 contingency and optimum relay characteristics - Entekhabi-Nooshabadi, Amir Mohammad; Hashemi-Dezaki, Hamed; Taher, Seyed Abbas (Applied soft computing, 2021)
There is a knowledge gap about the development of optimal coordination of microgrids, which considers all N-1 contingencies by using the smart selection of standard relay characteristics. This paper tries to fill such a knowledge gap by contributing to introduce a novel method to optimize the coordination of microgrids’ directional overcurrent relays (DOCRs), which smartly selects the time-current characteristic of relays and considers all system topologies. Achieving an optimal protection scheme of microgrids without any selectivity constraint under various topologies is the main purpose of this research. The proposed objective function of total operating time of DOCRs under various system topologies is linearized as the TDSs. The hybrid heuristic-linear programming algorithms (HHLPAs) are used to solve the mixed-integer non-linear programming (MINLP) problem. The decrease in the number of heuristic algorithm’s decision variables improves the performance of the proposed HHLPAs. The soft computing-based comparison of the hybrid genetic algorithm-linear programming (GA-LP) and the hybrid particle swarm optimization-linear programming (PSO-LP) is another contribution of this paper. About 80% decrease in the DOCRs’ operating time has been achieved by applying the proposed smart selection of standard relay characteristics (normally inverse, very inverse, and extremely inverse) in comparison to use of just normally inverse curve based on existing methods. The satisfaction of coordination constraints of optimum relay settings is validated based on the DIgSILENT protection simulations. [Display omitted] •Optimal coordination of microgrid relays considering N−1 contingency.•The smart selection of relay time-current characteristics.•The validation of the optimum results by DIgSILENT simulations.•The comparison of the GA-LP and PSO-LP results.•The decrease in the coordination constraints’ violations due to various topologies.